A significantly improved polymer||Ni(OH)2 alkaline rechargeable battery using anthraquinone-based conjugated microporous polymer anode. (July 2022) - Grieco, Rebecca; Molina, Antonio; Sanchez, Jaime S.; Patil, Nagaraj; Liras, Marta; Marcilla, Rebeca
Abstract: Alkaline rechargeable batteries (ARBs) are predicted to be an attractive solution for large-scale electrochemical energy storage applications. However, their advancement is greatly hindered by the lack of high-performance and sustainable anode that can stably operate in less-corroding, low electrolyte concentration. Herein, we report the first example of polymer ARB able to operate in low concentrate electrolyte (1м potassium hydroxide [KOH]) due to the employment of a robust anthraquinone-based conjugated microporous polymer (IEP-11) as anode. The assembled IEP-11||Ni(OH)2 achieves high cell voltage (0.98 V), high gravimetric/areal capacities (150 mAh/g/7.2 mAh/cm 2 at 3.5 and 65 mg/cm 2, respectively), long cycle life (22, 730 cycles, 960 h, 75% capacity retention at 20C), excellent rate performance (75 mAh/g at 50C) and low temperature operativity (75 mAh/g at −10 °C). Furthermore, rate capability, low-temperature performance and ability to prepare high mass loading anodes, along with low self-discharge is improved compared to conventional linear poly (anthraquinone sulfide) (PAQS) in commonly used 10 м KOH. This overall performance for IEP-11||Ni(OH)2 is not only far superior to that of PAQS||Ni(OH)2 owing to porous polymer's high specific surface area, combined micro-/mesoporosity and robust and mechanically stable three-dimensional (3D) architecture compared to the linear PAQS, but also surpass most of the reported organic||nickel [Ni]/cobalt [Co]/manganese [Mn] alkaline rechargeable batteries (ARBs). Graphical abstract: Image 1 Highlights: Alkaline batteries with commercial nickel (II) hydroxide [Ni(OH)2 ] cathode and anthraquinone polymer anodes were reported. Performance of linear polyanthraquinone sulfide (PAQS) vs. porous anthraquinone polymer (IEP-11) anodes were compared. Polymer battery in 1м potassium hydroxide (KOH) was successfully demonstrated for the first time with excellent performance. Porous IEP-11 outperformed linear PAQS, and also reported organic alkaline batteries.